COAST, LOWLAND, AND HIGHLAND: A GEOGRAPHICAL UNITY IN SUPPORTING THE ECONOMY OF CIREBON FROM XIX-XX CENTURY - Arovah, Eva Nur; Lubis, Nina Herlina; Dienaputra, Reiza; Nugrahanto, Widyo (History Department, Semarang State University and Historian Society of Indonesia, 2018)
Since 14th and 15th century, the kingdoms located among the islands of archipelago, including Cirebon, have involved in trading activities among the islands of archipelago or even international. Started from the fall of Majapahit and Demak kingdoms, the northern coastal areas of Java mostly are dominated by the rulers and Moslem traders. In 17th century, by the equal disintegration of traditional politics and taking over of the power of Cirebon Palace by VOC and the system and direction of policy which are made by the Dutch government, the sector-based trade in the coastal area of Cirebon becomes increasingly advanced and widespread. Started from the coastal area, in its development, the developing center trade becomes in hand with the developing of agricultural sectors in the lowlands and plantation in the highlands. By the historical method and structural approach from Fernand Braudel, this research is trying to explain CirebonÃ¢â‚¬â„¢s Geography as a synthesis that plays a role in Cirebon economic activity. No less important, archaeological evidences will be included as an attempt to identify the historical fact. Because in reality, the three regions (coastal area, agriculture and plantation) are a unity of the mutually bounded and have a reciprocal relationship in its contribution to the economic progress of the Dutch.Ã‚Â Semenjak abad ke-14 dan ke-15, kerajaan-kerajaan yang terletak di kawasan pesisir Nusantara, termasuk Cirebon, telah terlibat dalam perdagangan antarpulau Nusantara maupun perdagangan antarnegara. Dimulai semenjak runtuhnya Majapahit dan kejayaan Demak, kawasan pantai utara Jawa hampir seluruhnya dikuasai oleh para penguasa dan pedagang muslim. Memasuki abad ke-17, bersamaan dengan disintegrasi politik tradisional dan pengambil-alihan kekuasaan keraton Cirebon oleh VOC serta pola dan arah kebijakan yang dikeluarkan pemerintah Hindia Belanda, sektor perdagangan yang berpusat di kawasan pesisir Cirebon menjadi semakin mengikat dan meluas. Dimulai dari kawasan pesisir, dalam perkembangannya pengembangan pusat perdagangan menjadi beriringan dengan perkembangan pertanian di dataran rendah dan perkebunan di dataran tinggi. Dengan menggunakan metode penelitian sejarah dan pendekatan struktur sebagaimana yang dilakukan Fernand Braudel, penelitian ini mencoba mendeskripsikan geografis Cirebon sebagai sebuah sintesa yang berperan besar dalam kegiatan ekonomi Cirebon. Karena dalam kenyataannya tiga kawasan di atas merupakan suatu kesatuan yang saling terikat dan memiliki hubungan timbal balik dalam sumbanganya terhadap perkembangan ekonomi Hindia Belanda.Ã‚Â